Perancangan Key Performance Indicators (KPI) Menggunakan Metode Balanced Scorecard di PT. Aston System Indonesia - Febrinata -; Murman Budijanto; Irwan Iftadi (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2014)
High demand to the printer’s product also affecting the increase of companies that run in the printer sales and services. This makes the competition in the printer sales and services company getting higher. PT. Aston System Indonesia is one of the companies that run in the printer sales and services. In order to compete, companies are required to make improvements in all aspects. Therefore, it is necessary a performance measurement for measuring the performance of the company. This study used the Balanced Scorecard to develop Key Performance Indicators (KPI) as the reference performance measurement at PT. Aston System Indonesia. To determining KPIs are used the Pairwise Comparison method to weighted strategic objectives. The result of the research conducted 19 strategic objectives, 39 performance indicators and 10 KPIs.